1993
DOI: 10.1063/1.354745
|View full text |Cite
|
Sign up to set email alerts
|

Backward volume wave solitons in a yttrium iron garnet film (invited) (abstract)

Abstract: Phase properties of microwave magnetic envelope dark solitons in yttrium iron garnet thin films (abstract) Forward volume wave microwave envelope solitons in yttrium iron garnet films: Propagation, decay, and collision J. Appl. Phys. 76, 4274 (1994); 10.1063/1.357312 Forward volume wave microwave envelope solitons in yttrium iron garnet thin films: Peak profiles and multisoliton signatures (abstract)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 1 publication
0
4
0
1
Order By: Relevance
“…The oxidized amounts of ingested fructose ranged from 37.5% to 62.0%. Except in one study [60] which showed that fructose and glucose had similar oxidation rates (38.8% and 40.5%, respectively), the other studies all observed that glucose was oxidized faster than fructose under the exercise conditions [47,50,55,56,61-65]. A very interesting phenomenon noted is that when fructose and glucose are ingested together (including fructose-containing sucrose), the oxidation rates of the mixed sugars were faster than that of either one of them ingested alone at the same dosage.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The oxidized amounts of ingested fructose ranged from 37.5% to 62.0%. Except in one study [60] which showed that fructose and glucose had similar oxidation rates (38.8% and 40.5%, respectively), the other studies all observed that glucose was oxidized faster than fructose under the exercise conditions [47,50,55,56,61-65]. A very interesting phenomenon noted is that when fructose and glucose are ingested together (including fructose-containing sucrose), the oxidation rates of the mixed sugars were faster than that of either one of them ingested alone at the same dosage.…”
Section: Methodsmentioning
confidence: 99%
“…Under exercise conditions, Lecoultre et al [51] reported that 29% of ingested fructose (96 g) is converted to glucose when a steady state of carbohydrate flux was reached (1.7-2 hrs from the beginning of study). With repeated administration to achieve a high dose level and under exercise, Jandrian et al [50] reported that 55-60% of circulating glucose comes from fructose conversion during the latter half of the monitoring period. This data is similar to that observed by Delarue et al [49] who reported the amount of glucose synthesized from fructose was 57% of overall glucose appearance in the circulation after an ingestion of fructose at dosage of 1 g/kg bw, while the subjects were not under exercise.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to glucose during exercise, exogenous fructose has delayed the rate of intestinal absorption [154], lowering the rate of oxidation during exercise [155,156] possibly as a result of its slower absorption rate and the necessity for its conversion to glucose by the liver before oxidation [156]. The combination of fructose and glucose, however, is well absorbed during exercise [157] and may facilitate a higher oxidation than either of the two sugars ingested separately [158].…”
Section: Fructose and Exercisementioning
confidence: 99%
“…Было показано [7][8][9][10][11][12][13][14][15], что эффекты самовоздействия СВ при распространении в МК на частотах, отвечающих выполнению критерия (2), могут приводить к образованию модуляционной неустойчивости и образованию солитонов СВ. С другой стороны, известно, что в магнитных пленках дисперсия СВ выбором направления намагничивания [16][17][18][19] или металлизацией [20][21][22][23] может обеспечивать выполнение критерия (2) в отсутствие пространственной периодичности. Представляет интерес исследовать развитие эффектов самовоздействия СВ в МК в условиях, когда брэгговские резонансы формируются на участках дисперсионной зависимости f = f (k, |ϕ| 2 ), где выполнен критерий (2).…”
Section: Introductionunclassified